(untitled) - Onishchik, Arkady L. (Zurich, 2004)
The book is aimed at students in Lie groups, Lie algebras and their representations, as well as researchers in any field where these theories are used.
Keywords: Đại số học,Lie algebras,Semisimple Lie groups